The Role of Business Innovation in Increasing Company Competitiveness in the Global Market - Novita Sari Br Purba (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the role of business innovation in improving corporate competitiveness in the global market. The research method used is a quantitative approach with descriptive and verification analysis techniques. Data were collected through questionnaires distributed to 80 respondents who are business actors and managers of companies operating in the global market. Data analysis was conducted using simple linear regression. The results of the study indicate that business innovation has a positive and significant influence on corporate competitiveness with a regression coefficient value of 0.745 and a significance level of 0.000. The coefficient of determination value of 0.68 indicates that business innovation contributes 68% to increasing corporate competitiveness. Product, process, marketing, and business model innovations have been proven to increase a company's competitive advantage in the global market. The conclusion of this study is that business innovation is a very important strategic factor in improving corporate competitiveness. Therefore, companies need to develop a culture of innovation and integrate innovation into their business strategies to face global competition.